2008
DOI: 10.1644/07-mamm-a-345.1
|View full text |Cite
|
Sign up to set email alerts
|

Use of Natural Licks by Four Species of Ungulates in Northern British Columbia

Abstract: Use of licks influences the movements and distribution of ungulates. We recorded attendance patterns, duration of visits to licks, and time spent licking by 4 ungulate species at wet and dry licks to examine possible influences on the timing of use of licks in northern British Columbia, Canada. Within-species licking intensity (based on regressions between time spent licking per visit and duration of visits to licks) was higher for elk (Cervus elaphus) than for moose (Alces alces) at wet licks, and higher for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 30 publications
5
53
2
3
Order By: Relevance
“…[4], [14], [18]). Recently developed camera traps are capable to record in video formats and can operate continuously for up to 6-months, which enabled recordings of animal activities over a very long period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4], [14], [18]). Recently developed camera traps are capable to record in video formats and can operate continuously for up to 6-months, which enabled recordings of animal activities over a very long period.…”
Section: Discussionmentioning
confidence: 99%
“…In a predator-prey relationship, spatial overlaps may be important in predicting encounter probabilities [2]. Studies have documented the use of salt licks by a wide range of species guild, such as carnivores, herbivores-frugivores, insectivores and omnivores and ungulates [3], [4]. A salt lick in general, refers to a mineral rich site which is frequently and actively visited by animal for the purpose of consuming minerals deposited there, through licking or geophagy [3]- [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have noted that the primary role of licks is the provision of sodium (Weeks and Kirkpatrick 1976;Fraser and Reardon 1980;Moe 1993;Rick et al 2003;Ayotte et al 2008). Since 20th century, both managers and researchers have begun to establish artificial mineral or salt licks in areas where natural licks are absent or uncommon and this has been proved very helpful for herbivores to overcome the Na deficiency (Schultz and Johnson 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Atwood and Weeks (2002) explored the sex and age pattern of mineral lick uses of white-tailed deer (Odocoileus Virginianus) and found that females came to licks very often during lactation and males visited licks consistently over the study period. Ayotte et al (2008) compared lick use differences between two sexes of moose (Alces alces) and wapiti (Cervus canadensis) and found that attendance by female wapiti coincided with lactation demand while no clear differences in patterns of licking activity existed between the two sexes of moose.…”
Section: Introductionmentioning
confidence: 99%